Identifying Client Targets for Improved Mobilization and Uptake of Integrated Family Planning and Reproductive Health in Environmental Programs in Kenya - Obat, Edmon; Schaefer, Krista; Opiyo, Mumma; Otieno, George; Windindi, Henrietta; Omuodo, Derick; Mehta, Supriya D. (Frontiers in Global Women's Health, 2021)
Background: We conducted a population health environment program in Lake Victoria Basin (LVB) and assessed incorporation and integration of family planning with environmental conservation. Methods: Routine program data were collected from clients by community-based distributors from four environmental community-based organizations. Multivariable regressions identified factors associated with distribution of: (1) oral contraceptive pills to women, (2) male condoms, and (3) integrated family planning and environmental messaging. Results: April 2015 through May 2016, 10,239 client encounters were completed, with 56% made by men. We distributed contraceptive pills at 28% of client encounters. Multivariable modeling showed this was more likely for women <40 years old (p < 0.001) and was less likely for women attending household (30%) and group sessions (46%) compared to individual sessions (p < 0.001). Male condoms were distributed at 73% of client encounters; (p < 0.01, all) women were half as likely to receive condoms than men, and single and widowed clients were more likely than married clients to receive condoms. Integrated messaging occurred at 89% of client encounters, and was 85% more likely for women, increased with client age, and was less likely for single and widowed persons. Exit interviews with 87 clients (42% male, 58% female) confirmed program data by report of commodities received: 27% contraceptive pills, 75% male condoms, 91% integrated messaging. Conclusions: Partnership with environmental conservation organizations effectively expanded family planning and reproductive health to non-traditional audiences and men among rural communities surrounding LVB-Kenya. Specific client subgroups can be targeted for improved mobilization and uptake of services.